2017
DOI: 10.1007/978-3-319-57348-9_3
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Problems Among Greek Perioperative Nurses in Regional Hospitals in Southern Peloponnese

Abstract: The surgery unit is a particularly labor-intensive environment in the hospital. Studies reflect the correlation of labor risk factors for musculoskeletal injuries among nurses but few have investigated the relationship to perioperative nurses. The purpose of this study is the identification and definition of ergonomic risk factors in the operating room and their connection with musculoskeletal disorders in perioperative nurses in regional hospitals in Greece. Forty four Greek perioperative nurses working in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
1
4
0
3
Order By: Relevance
“…1) The studies were published from 2007 to 2019. They all used a cross-sectional design but Bakola et al [29] that used a prospective design and Keriri et al [20] that added a nested case control study to the cross-sectional design. The total sample of perioperative nurses included was 3405; most were female (77%), with a mean age of 37.8 years.…”
Section: Resultsmentioning
confidence: 99%
“…1) The studies were published from 2007 to 2019. They all used a cross-sectional design but Bakola et al [29] that used a prospective design and Keriri et al [20] that added a nested case control study to the cross-sectional design. The total sample of perioperative nurses included was 3405; most were female (77%), with a mean age of 37.8 years.…”
Section: Resultsmentioning
confidence: 99%
“…Musculoskeletal diseases (MSDs) refer to the state of discomfort, disability, damage, or persistent pain in support systems, including the nerves, muscles, bones, joints, ligaments, tendons and blood vessels [1]. Musculoskeletal diseases are widespread worldwide and are considered to be a major occupational injury, both in developed and developing countries [2,3], and the prevalence is especially high among nurses [4,5]. Saberipour B et al [2] and Habibi E et al [6] reported a prevalence rate of 84.2% and 87.6% for musculoskeletal diseases among Iranian nurses, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the nature and frequency of the tasks performed, musculoskeletal disorders are particularly common in perioperative staff 3,18 . In this study, 88 per cent of participants had experienced musculoskeletal discomfort (aches and pain) in the last seven days.…”
Section: Discussionmentioning
confidence: 99%